Insights into the genomic evolution of insects from cricket genomes - Guillem Ylla; Taro Nakamura; Takehiko Itoh; Rei Kajitani; Atsushi Toyoda; Sayuri Tomonari; Tetsuya Bando; Yoshiyasu Ishimaru; Takahito Watanabe; Masao Fuketa; Yuji Matsuoka; Austen A. Barnett; et al. (Communications Biology, 2021)
Ylla, Extavour et al. use genomic data from crickets to investigate the evolution of large genome sizes and DNA methylation events in insects. Their findings indicate that transposable element activity drove genome expansion in hemimetabolous insects, such as crickets and grasshoppers, and that DNA methylation is predominant in conserved genes.